Reading reference - Felder, Ekkehard; Jacob, Katharina; Busse, Beatrix; Große, Sybille; Gvozdanović, Jadranka; Lobin, Antje; Lobin, Henning (Handbuch europäische Sprachkritik online, 2025)
Language ideologies, the linguistic and culturally specific shaping of which is the primary focus of this Handbook, are an integral part to the various forms of language criticism. Language ideologies represent social indexicality: they refer to socio-culturally and discursively relevant language-reflective or language-critical individuals and collectives, while at the same time serving as action-guiding templates for attempts and procedures to achieve language standardisation. In this fifth volume, we elucidate the interrelationship between language ideologies and language criticism, i.e. concrete forms of (assessing) evaluative language reflection, and their intellectually and socially effective concepts.